Pengembangan LKPD Berbasis Etnomatematika Kain Lunggi Sambas dengan Model Pembelajaran Inkuiri Terbimbing Pada Materi Pola Bilangan Kelas VIII - Umaroh, Anisa; Nandita, Aura; Mawarsar, Venissa Dian (Journal of Lesson Study in Teacher Education, 2025)
This study aims to develop a Student Worksheet (LKPD) based on the ethnomathematics of Kain Lunggi Sambas using the Guided Inquiry learning model for the number pattern material for Grade VIII students. The LKPD was developed using the Research and Development (R&D) method with a modified ADDIE framework, including the analysis, design, and development stages, with a focus on the preparation of content, activities, illustrations, and an appealing layout. The motifs of Kain Lunggi were used as a local cultural context to help students observe patterns, formulate general rules, and relate mathematical concepts to real-life situations. The LKPD was designed with activities emphasizing observation, reasoning, data interpretation, and conclusion drawing according to the Guided Inquiry stages, enabling students to learn independently and contextually. By incorporating cultural context into learning, this LKPD has the potential to enhance meaningful learning experiences, facilitate conceptual understanding, improve mathematical representation skills, and foster appreciation and love for local culture. Although it has not yet been formally tested or validated, this study is expected to serve as a basis for developing other ethnomathematics-based learning media.